Population dynamics and fishery biology of the yellow-edged lyretail grouper Variola louti (Forsskål, 1775) along the eastern coast of the Red Sea - Kadengal, Sirajudheen Thayyil; Okba, Zahra; Muthu Palani, Goutham Bharathi; Charles, Santhosh; Adam, Adel M. S.; Boulila, Nesrine; Tıraşın, Eyüp Mümtaz; Dimech, Mark (Frontiers in Marine Science, 2025)
The yellow-edged lyretail grouper, Variola louti, is ecologically and commercially important in the Red Sea. As a carnivorous species, V. louti plays a vital role in maintaining coral reef ecosystem health. Annually, an estimated 260 tonnes of V. louti are landed along the Saudi Arabian Red Sea coast, contributing approximately 6.5 million USD to the national economy. Given its significance, effective fishery management is crucial for sustainability. This study assessed the growth, maturity, and mortality of V. louti using fishery-dependent samples collected from the eastern Red Sea (February 2022–December 2024). Fork length (FL, n = 7,087) ranged from 10.5 to 64.3 cm, while total weight (W, n = 2,629) varied from 53 to 2,910 g. The FL–W relationship for both sexes combined was W = 0.0117×FL3.1. Von Bertalanffy growth parameters, based on sagittal otolith readings, were FL∞ = 62.28 cm, K = 0.12 year−1, and t0 = −2.26 years. Median FL at first maturity was 24.98 cm, with no significant sex differences. Mean natural mortality (M), derived from three different methods, was 0.243 year−1. Total mortality (Z), estimated using a linearized exponential decay model, was 0.38 year−1. Based on these Z and M estimates, fishing mortality (F) was calculated as 0.137 year−1. Yield-per-recruit and spawning potential ratio analyses indicate that the current F estimate places the stock near the target reference point. The current exploitation rate (E = 0.36) remains well below the limit reference point of 0.5. The V. louti fishery encompasses a broad FL range and multiple age groups, with immature individuals comprising less than 12% of total landings. However, according to the minimum landing size of 33 cm FL set by Saudi Arabian fisheries regulations, 47% of the total catch consisted of mature fish aged 2–3 years but below this threshold (25 cm ≤ FL < 33 cm), while only 41% met the legal-size requirement (FL > 33 cm). The high proportion of legally undersized individuals in landings underscores the need for ongoing monitoring and additional management measures, such as catch quotas, seasonal restrictions, and fishing effort reduction, to ensure long-term stock sustainability.